THE TRANSMUTED GAMMA-GOMPERTZ DISTRIBUTION - AzZwideen, Rwabi; Zou’bi, Loai M. Al (International Journal of Research -GRANTHAALAYAH, 2020)
This article introduces a four-parameter probability model which represents a gener- alization of the the Gamma-Gompertz distribution using the quadratic rank trans- mutation map. The proposed model is named the Transmuted Gamma-Gompertz distribution. We provide explicit expressions for its statistical properties, moment generating function, quantile function, the order statistics, the quantile function and the median. We estimate the parameters of the distribution using the maximum likelihood method of estimation.